The Impact of Different Fiber Placement Techniques on the Fracture Resistance of Premolars Restored with Direct Resin Composite, In Vitro Study - Reham Hesham Ibrahim; Dina Wafik ElKassas; Sameh Mahmoud Nabih; Mennatallah Naguib Salem; Rasha Haridy (Journal of Functional Biomaterials, 2025)
Fiber-reinforced composites (FRCs) are recognized for enhancing the fracture resistance of structurally compromised teeth. However, the optimal orientation and placement of fibers in direct resin composite restorations remain under debate. This study aimed to evaluate the fracture resistance of maxillary premolars with mesio-occluso-distal (MOD) cavities restored using polyethylene fibers with different placement techniques, compared to conventional incremental composite restoration. Methods: Sixty intact maxillary premolars were randomly assigned to six groups (n = 10). Group 1: intact teeth (positive control); Group 2: MOD cavity without restoration (negative control); Group 3: MOD cavity restored with nanohybrid composite using the incremental technique; Group 4: polyethylene fiber placed on the pulpal floor; Group 5: fiber placed circumferentially along cavity walls (wall-papering technique); Group 6: fiber placed buccolingually in an occlusal groove (occlusal splinting). Fracture resistance was assessed using a universal testing machine. Failure mode was also analyzed. Results: Group 6 (occlusal splinting) exhibited the highest fracture resistance (1137.72 ± 316.20 N), significantly exceeding Group 3 (546.93 ± 59.89 N) and other fiber-reinforced groups (p < 0.05). Failure mode analysis revealed no significant differences between the fiber-reinforced groups and the intact teeth. Group 6 also had the highest percentage of restorable fractures (90%). Conclusions: Incorporating polyethylene fibers, especially through occlusal splinting, significantly improves fracture resistance in MOD-restored maxillary premolars. This technique may offer a promising alternative to conventional composite restorations in structurally weakened posterior teeth.